Nurses’ perceptions, experiences, and practices regarding human papillomavirus vaccination: results from a cross-sectional survey in Montana - Juthika Thaker; Alexandria N. Albers; Sophia R. Newcomer (BMC Nursing, 2023)
Abstract Background Nationally, much of the focus on improving human papillomavirus (HPV) vaccine uptake has been on effective strategies that physicians use to promote vaccination. However, in large, predominately rural states like Montana, nurses and medical assistants play critical roles in immunization services delivery, and their viewpoints are imperative in designing strategies to increase vaccination rates. We conducted a cross-sectional, descriptive study to determine nurses’ perceptions, experiences, and practices regarding human papillomavirus vaccination in a rural and medically underserved region of the United States. Methods We designed, pilot-tested, and disseminated an online survey instrument to nurses and medical assistants working in clinics participating in the Vaccines for Children program in Montana. The online surveys were administered from November 2020 to March 2021. Survey questions focused on clinic vaccination practices, respondents’ perceptions of the HPV vaccine, perceived barriers to vaccine uptake, and general opinions on potential strategies to improve HPV vaccination rates. Results We analyzed data from 227 respondents. Overall, 90% of nurses strongly agreed or agreed that the HPV vaccine is important and had confidence in the vaccine’s safety. More nurses reported experiencing greater parental vaccine refusal or delay for male patients regardless of age. About 53.7% of nurses reported that their clinics had reminder/recall systems to encourage parents to bring their children for vaccination. Nurses identified misinformation from social media, infrequent wellness visits, and vaccine safety concerns as barriers to HPV vaccine uptake. Conclusions Study findings identified several promising initiatives to accelerate vaccination in primarily rural states like Montana, including promoting widespread adoption of reminder/recall systems, training nurses in evidence-based techniques to provide strong vaccine recommendations, and leveraging social media to disseminate consistent messages about the HPV vaccine recommendations for both sexes and its role in cancer prevention.